Analisis water footprint pada budidaya pakcoy dengan sistem irigasi bawah permukaan pocket fertigation - Putri Agustina Hotmatua Hutabalian; Chusnul Arif (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2023)
Limited water resource and the decrease in the plant productivity of the bok choy (Chinese white cabbage) causes the need for appropriate irrigation technology. Pocket fertigation, as an innovative irrigation technology, is develop from previous a ring irrigation system and it is expected to increase crop and water productivity. This study aims to analyze the water footprint of the bok choy plant using a pocket fertigation irrigation system with various scenarios, and to determine the optimal irrigation system. The research was conducted in April-June 2022 at Kinjiro Farm, Bogor City. The research steps included land preparation, data collection, data processing, and water footprint analysis. Irrigation scenario design is influenced by factors of pocket fertigation (P1) and conventional (P2) irrigation systems, as well as water supplied based onetime evaporation (A1) and two times evaporation rates. The total water footprint in scenarios P1A1, P2A1, P1A2, and P2A2 are 251.72 m3/ton, 231.56 m3/ton, 295.69 m3/ton and 222.16 m3/ton respectively with the highest irrigation efficiency occurs in the P2A1 scenario, so further development of pocket fertigation is needed to minimize the water footprint and increase water productivity.